1992
DOI: 10.1093/oxfordjournals.aje.a116277
|View full text |Cite
|
Sign up to set email alerts
|

Age Interacts with Heaviness of Smoking in Predicting Success in Cessation of Smoking

Abstract: There is conflicting evidence regarding the relation between heaviness of smoking and the likelihood of quitting smoking. We investigated this issue using the data set of the 1986 Adult Use of Tobacco Survey, a telephone survey of the smoking behavior of noninstitutionalized, civilian, US adults aged greater than 16 years. Analyses were based on a subsample of 4,383 individuals who had made a serious attempt to stop smoking 1-10 years before the survey. Among younger smokers, the lighter smokers (less than 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(48 citation statements)
references
References 0 publications
3
44
1
Order By: Relevance
“…55 During 1967During -1970, when the Fairness Doctrine antismoking messages appeared on television and radio, cessation increased for all four groups but especially for white males and females. The data in Figure 1 and many of the population-based cross-sectional studies 2,17,18,22,26,[48][49][50][51][52][53] likely reflect, at least in part, the "head start" that white males and females had in terms of quitting smoking. Among all four groups, cessation rates increased during the 1970's and 1980's, 54 which is consistent with the increasing slopes for both whites and African Americans that are seen in Figure 1.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…55 During 1967During -1970, when the Fairness Doctrine antismoking messages appeared on television and radio, cessation increased for all four groups but especially for white males and females. The data in Figure 1 and many of the population-based cross-sectional studies 2,17,18,22,26,[48][49][50][51][52][53] likely reflect, at least in part, the "head start" that white males and females had in terms of quitting smoking. Among all four groups, cessation rates increased during the 1970's and 1980's, 54 which is consistent with the increasing slopes for both whites and African Americans that are seen in Figure 1.…”
Section: Discussionmentioning
confidence: 89%
“…As shown in Figure 1 and previously by Fiore and his colleagues, 3 the percentage of ever-smokers who have quit has consistently been higher among whites than African Americans, a finding that is supported from studies in individual years. 2,17,18,22,26,[48][49][50][51][52][53] One study, 51 and an analysis presented in Table 34 of Chapter 2 of the 1998 Report of the Surgeon General, 2 indicate that the differences by race persist even after statistical adjustment was made for variables such as age, gender, and indicators of socioeconomic status (SES). Burns and his colleagues presented birth cohort analyses of whites and African Americans born during the 20th century that help explain these disparities.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Cross-sectional studies of smoking or drinking habits have been reported in many countries including Japan. [5][6][7][8][9][10][11][12] However, longitudinal changes in smoking and drinking habits and their related factors have also been investigated, [13][14][15][16][17][18][19] but such few studies have been conducted among Japanese. 20 If exposure data in cohort studies are only measured at baseline even though exposure histories change significantly after baseline, the estimates of relative risk may be biased due to insufficient information regarding exposure.…”
mentioning
confidence: 99%
“…The findings of previous studies mention that the younger the initial smoking age is the harder to quit smoking. In other words, the possibility to quit smoking is inversely related to initial smoking age (Coambs, Seline, and Kozlowski, 1992;Breslau and Peterson, 1996). This research interestingly finds that the willingness to stop smoking occurs to adolescents with younger initial smoking age (16.62 years old); compared to ones not willing to quit smoking (17.01 years old).…”
Section: Descriptive Analysismentioning
confidence: 63%
“…The earlier one started to smoke, the harder for him/her to stop the habit.In other words, the possibility for one to stop smoking is inversely related to initial smoking age (Coambs, Seline, and Kozlowski, 1992;Breslau and Peterson, 1996). If one does not start to smoke as an adolescent, it is highly unlikely for him/her to smoke (US Department of Health and Human services, 1994).…”
Section: Introductionmentioning
confidence: 99%